Kontribusi Pemikiran Moh. Mahfud MD Konfigurasi Politik dalam Merespon Dinamika Keislaman dan Kebangsaan - Moh. Wardi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
Moh. Mahfud MD is an academic figure and role model that provides scientific insights for all components of citizens about the life of the nation and religion in the context of Indonesia. He is a charismatic figure that can be accepted in every class, moderate, inclusive and followed by a comprehensive analysis which always becomes a reference and responds to contemporary issues in the nation and religion. Polemic about the rise of khilafa>h in Indonesia, that the serious struggle to enforce formally Islamic law / Islamic law, has been done by the founding of our country (founding parents). In the end the agreement was to establish a nation state based on Pancasila. this agreement must be carried out consistently because it contains the values ​​and philosophical content of mîtsâqan ghalîzha (noble deal) and we must not betray it. The theory of 'political configuration' in the view of Mahfud MD is the dissemination of political energy to be able to incorporate the substantive values ​​of universal Islamic teachings into the formal law (positive law) prevailing in Indonesia. According to Moh. Mahfud MD that law is a political product, so the character of legal products is determined by the balance of political forces (political configuration) that gave birth. So Muslims should be able to sit in government institutions, both legislative, executive and judiciary.